Review of Antilliaans erfgoed - Phaf-Rheinberger, Ineke (2022)
This is a two-volume review of West Indian heritage: Antilliaans erfgoed, volume 1: Toen en un and volume 2: Nu en verder, edited by Gert Oostindie & Alex van Stipriaan, in Leiden, Netherlands, by Leiden University Press, in 2021. The first consists of 288 pages and the second of 282 pages, they have the ISBN 978 90 8728 355 1+2